2021
DOI: 10.2166/wpt.2021.036
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of microplastics fate in the wastewater treatment plants: frequency and removal of microplastics by microfiltration membrane

Abstract: In this research, the fate and removal of microplastics (MPs) entering and leaving in wastewater treatment plant (WWTP) was investigated. Additionally, the application of microfiltration membrane technique for MPs removal were evaluated. In the first phase, the quantity, type and size of the MPs were studied from three different points of the WWTP. The results showed that the average amount of MPs entered into the WWTP, accumulated in thesludge matrix and discharged from the effluent were 206, 183 and 94 MP/L,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It has been estimated that typical microplastic removal rates range from 80% to 95%, with some plants achieving up to 99% removal (Kalčíková et al 2017, Mintenig et al 2017). It was observed that the application of microfiltration during wastewater treatment could achieve microplastic removal efficiency up to 98% (Yahyanezhad et al 2021).…”
Section: Types and Sourcesmentioning
confidence: 99%
“…It has been estimated that typical microplastic removal rates range from 80% to 95%, with some plants achieving up to 99% removal (Kalčíková et al 2017, Mintenig et al 2017). It was observed that the application of microfiltration during wastewater treatment could achieve microplastic removal efficiency up to 98% (Yahyanezhad et al 2021).…”
Section: Types and Sourcesmentioning
confidence: 99%